Identification and Phenotypic Evaluation of Microbes Isolated from Breast and Formula-fed Infants Delivered Either Vaginally or by Cesarean Section (P11-075-19). (13th June 2019) - Kim, Heejin; Mackie, Roderick; Cann, Isaac; Donovan, Sharon
Abstract: Objectives: Many factors influence the development of the infant microbiota. Based on 16S rDNA sequencing information, the type of feeding, i.e., breast vs formula, has been shown to be the most important factor, with route of delivery having transient effects in the early postpartum period. However, few recent studies have isolated individual strains from human infants or have investigated the functional properties of the infant gut microbes. We used a 2 × 2 experimental design with the goal of determining how diet and delivery interact to shape infant microbiota composition and metabolic activity. Methods: Fresh fecal samples were collected from 3-month-old infants who were either exclusively breast- (BF) or formula-fed (FF) and cesarean- (CD) or vaginally-delivered (VD). Samples were diluted and plated on two types of media: Gut Microbiota Medium (GMM) or MRS medium. Individual colonies were picked, purified and their 16S rRNA gene sequenced for identification. These isolates were screened for growth on various carbon substrates, including human milk oligosaccharides, prebiotics and volatile fatty acids for 24–36h. Medium supernatant was collected and metabolic profiles assessed by HPLC. Results: More than 150 bacterial strains have been isolated and identified from infant fecal samples to date. Isolates from BF/VD fecal samples were predominantly from the phylum Actinobacteria (dominated with Bifidobacterium ) followed by Firmicutes and Proteobacteria. In contrast, isolates from FF/VD or FF/CD infants were primarily from the phylum Firmicutes with only a few Actinobacterial and Proteobacterial isolates. Quantitatively, most isolates represented the genera Bifidobacterium, followed by Enterococcus, and Ruminococcus . On-going phenotypic evaluation of the isolated strains for the growth and utilization of various carbon sources and metabolic profiles will provide insight into species- and strain-specific utilization of common prebiotics in human milk and infant formula. Conclusions: This collective data will provide novel insights on how the physiological and metabolic function of the infant gut microbiota is influenced by route of delivery and early infant nutrition. Funding Sources: NIH R01DK107561.